c-Type cytochrome biogenesis can occur via a natural Ccm system lacking CcmH, CcmG, and the heme-binding histidine of CcmE. - Goddard, A; Stevens, J; Rao, F; Mavridou, D; Chan, W; Richardson, D; Allen, J; Ferguson, S (2010)
The Ccm cytochrome c maturation System I catalyzes covalent attachment of heme to apocytochromes c in many bacterial species and some mitochondria. A covalent, but transient, bond between heme and a conserved histidine in CcmE along with an interaction between CcmH and the apocytochrome have been previously indicated as core aspects of the Ccm system. Here, we show that in the Ccm system from Desulfovibrio desulfuricans, no CcmH is required, and the holo-CcmE covalent bond occurs via a cysteine residue. These observations call for reconsideration of the accepted models of System I-mediated c-type cytochrome biogenesis.